Optimization of Timing of Maternal Pertussis Immunization From 6 Years of Postimplementation Surveillance Data in England. (12th August 2022) - Amirthalingam, Gayatri; Campbell, Helen; Ribeiro, Sonia; Stowe, Julia; Tessier, Elise; Litt, David; Fry, Norman K; Andrews, Nick
Abstract: Background: England's third-trimester maternal pertussis vaccination, introduced in October 2012, was extended to the second trimester in 2016. Maternal vaccination provides high protection against infant disease, but routine second-trimester vaccination has not previously been assessed. Methods: National laboratory-confirmed pertussis case surveillance determined vaccination history, maternal vaccination history and hospitalization. Pertussis hospital admissions between 2012 and 2019 were extracted from the Hospital Episode Statistics data set. Vaccine effectiveness (VE) was calculated for pertussis case patients born between October 2012 and September 2018 using the screening method and matching with a nationally representative data set. Results: Higher coverage was observed after earlier maternal vaccination with approximately 40% of pregnant women vaccinated ≥13 weeks before delivery. Cases and hospitalizations stabilized at low levels in younger infants but remained elevated in older infants, children, and adults. No deaths occurred in infants with vaccinated mothers after 2016. Of 1162 laboratory-confirmed pertussis cases in the study, 599 (52%) were in infants aged <93 days: 463 (77%) with unvaccinated and 136 (23%) with vaccinated mothers. The VE was equivalent in infants with mothers vaccinated at different gestational periods except in those with mothers vaccinated between 7 days before and 41 days after delivery. Children whose mothers were unvaccinated but with vaccination in a previous pregnancy had a VE against disease of 44% (95% confidence interval, 19%–75%). There was no increased disease risk after primary vaccination in children with mothers vaccinated at least 7 days before delivery. Conclusions: National policy recommending vaccination in the second trimester increased earlier maternal vaccine uptake with sustained high VE and impact against early infant disease. Abstract : We found no statistically significant difference in vaccine effectiveness against infant pertussis by timing of maternal vaccination given >7 days before delivery. Effectiveness against disease, hospitalization, and death was high, with no reduced protection after primary vaccination in children with vaccinated mothers.